Several early interventions for ectopic maxillary canines. - Carlos Astorga; Felipe Donoso; Claudia Fierro; Antonieta Pérez (Universidad de Concepción., 2012)
Maxillary canine impactation is often encountered in orthodontic clinical practice and the aetiology is associated to genetic factors as well as local space factors. If preventive treatment is not started in ectopic maxillary canines, some possible consequences may occur, such as resorption of the roots of the neighboring permanent teeth, cysts, ankylosis and expensive surgical and orthodontic treatment. The aim of this review was to preset several early treatment modalities for ectopic maxillary canines based on recent scientific evidence. Four are the most important: Only extractions intervention, extraction of deciduous canines with cervical pull headgear, active intervention in late mixed dentition and active intervention in early mixed dentition. These different modalities showed a greater increasing the rate of normal eruption of ectopic canines ( 80-97%). The extraction of primary canine alone is still an effective method to prevent canine impactation, whose success rate would be increased if some other method interceptive is added.